1975
DOI: 10.1113/expphysiol.1975.sp002312
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Renal Haemodynamics and Electrolyte Excretion During Acute Hyperkalaemia in Conscious Adrenalectomized Sheep

Abstract: The p-aminohippurate (PAH) clearance, inulin clearance and the excretion of electrolytes by 10 adrenalectomized sheep were measured before, during and after the infusion of 0*43 M-KCl at 2 ml./min for 2 hr. The PAH clearance increased as the plasma potassium concentration increased up to approximately 6'0 m-mole/l. Further increases in plasma potassium were associated with a progressive return of the PAH clearance to or below the pre-infusion levels. At its maximum the PAH clearance was 1-228 ±0-032 (S.E. of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

1976
1976
1998
1998

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…In the conscious adrenalectomized sheep changes in renal plasma flow and glomerular filtration rate during hyperosmotic potassium chloride infusion were consistent with the vascular resistance of the kidney being lowered by the acute hyperkalaemia [Beal, Budtz-Olsen, Clark, Cross and French, 1975]. In contrast to animals in the anaesthetized state the conscious animal has full neural control of peripheral resistance and cardiac rate and thus has a capability to oppose 297 c…”
mentioning
confidence: 63%
See 2 more Smart Citations
“…In the conscious adrenalectomized sheep changes in renal plasma flow and glomerular filtration rate during hyperosmotic potassium chloride infusion were consistent with the vascular resistance of the kidney being lowered by the acute hyperkalaemia [Beal, Budtz-Olsen, Clark, Cross and French, 1975]. In contrast to animals in the anaesthetized state the conscious animal has full neural control of peripheral resistance and cardiac rate and thus has a capability to oppose 297 c…”
mentioning
confidence: 63%
“…As arterial BP is a balance between cardiac output and peripheral resistance the sheep with the higher initial BP levels presumably responded to theinitiationofhyperkalaemia with a relatively greater fall in peripheral resistance than the lower BP animals which was not fully compensated for by the increase in heart rate and, since the pulse pressure did not fall, by the increase in cardiac output. Further evidence of increased cardiac output at these levels of hyperkalaemia is provided by measurement of plasma and blood flows through various regional circulations in conscious sheep which have demonstrated that during the early part of a potassium infusion, the hyperkalaemia was associated with increased plasma and blood flows [Beal et al, 1975;Beal, 1976]. In the sheep with the lower initial BP levels the increase in cardiac output as reflected by the increase in heart rate not only compensated for any vasodilation but in many instances was an over-compensation which resulted in the tendency for the arterial BP to rise in these animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous studies in sheep have shown that acute hyperkalaemia, of the level produced in these experiments, increases cardiac output and blood flow to many tissues and causes diuresis (Beal et al 1975;Beal1976a, 1976b. All of these effects would favour increased clearance of insulin from the circulation and a reduction in plasma concentration rather than the converse.…”
Section: Discussionmentioning
confidence: 99%
“…By performing the present experiments on adrenalectomized sheep the possible intervention of endogenous adrenal steroids released as a result of the potassium infusion was prevented. As judged from salivary sodium/potassium ratios the effect of the DOCA maintenance injection reaches maximum and returns to sodium-replete ratios within 6-8 h of injection (Beal, Budtz-Olsen, Clark, Cross & French, 1975) so that during these experiments which started 18-20 h after the maintenance injection the concentrations of circulating steroids from exogenous sources would be expected to be low and falling relatively slowly.…”
Section: Discussionmentioning
confidence: 99%